Entrustment Decision Making in the Core Entrustable Professional Activities: Results of a Multi-Institutional Study. (30th March 2022) - Brown, David R.; Moeller, Jeremy J.; Grbic, Douglas; Biskobing, Diane M.; Crowe, Ruth; Cutrer, William B.; Green, Michael L.; Obeso, Vivian T.; Wagner, Dianne P.; Warren, Jamie B.; Yingling, Sandra L.; Andriole, Dorothy A.
Abstract : Purpose: In 2014, the Association of American Medical Colleges defined 13 Core Entrustable Professional Activities (EPAs) that all graduating students should be ready to do with indirect supervision upon entering residency and commissioned a 10-school, 5-year pilot to test implementing the Core EPAs framework. In 2019, pilot schools convened trained entrustment groups (TEGs) to review assessment data and render theoretical summative entrustment decisions for class of 2019 graduates. Results were examined to determine the extent to which entrustment decisions could be made and the nature of these decisions. Method: For each EPA considered (4–13 per student), TEGs recorded an entrustment determination (ready, progressing but not yet ready, evidence against student progressing, could not make a decision); confidence in that determination (none, low, moderate, high); and the number of workplace-based assessments (WBAs) considered (0–>15) per determination. These individual student-level data were de-identified and merged into a multischool database; chi-square analysis tested the significance of associations between variables. Results: The 2, 415 EPA-specific determinations (for 349 students by 4 participating schools) resulted in a decision of ready (n = 997/2, 415; 41.3%), progressing but not yet ready (n = 558/2, 415; 23.1%), or evidence against student progression (n = 175/2, 415; 7.2%). No decision could be made for the remaining 28.4% (685/2, 415), generally for lack of data. Entrustment determinations' distribution varied across EPAs (chi-square P < .001) and, for 10/13 EPAs, WBA availability was associated with making (vs not making) entrustment decisions (each chi-square P < .05). Conclusions: TEGs were able to make many decisions about readiness for indirect supervision; yet less than half of determinations resulted in a decision of readiness to perform this EPA with indirect supervision. More work is needed at the 10 schools to enable authentic summative entrustment in the Core EPAs framework.